The Ethics and Efficacy of Selling National Citizenship - Borna, Shaheen (Journal of business ethics, 2002)
The inevitable global marketplace creates a need for freer movement of labor. The question is not whether this movement will occur but how it will be implemented. This paper discusses the idea of selling citizenship rights as an alternative approach for allocating immigration and permanent residency. First presented is the rationale for using the market approach to selling citizenship. Next the political, country image, economic, and ethical implementation issues of the proposal are discussed. And last, selling citizenship is discussed in terms of ethical theory and frameworks.